Utilization of certain method from the field of data mining - Půlpán, Zdeněk (Univerzita Pardubice, 2009)
The paper describes the methodology of the so-called data mining on the example of a "healthy-ill" ensemble.
Keywords: Data Mining; flexible data management; statistical models; methodology